Transcription factor TFEB cell-autonomously modulates susceptibility to intestinal epithelial cell injury in vivo. Issue 1 (December 2017) - Murano, Tatsuro; Najibi, Mehran; Paulus, Geraldine; Adiliaghdam, Fatemeh; Valencia-Guerrero, Aida; Selig, Martin; Wang, Xiaofei; Jeffrey, Kate; Xavier, Ramnik; Lassen, Kara; Irazoqui, Javier
Abstract Understanding the transcription factors that modulate epithelial resistance to injury is necessary for understanding intestinal homeostasis and injury repair processes. Recently, transcription factor EB (TFEB) was implicated in expression of autophagy and host defense genes in nematodes and mammalian cells. However, thein vivo roles of TFEB in the mammalian intestinal epithelium were not known. Here, we used mice with a conditional deletion ofTfeb in the intestinal epithelium (Tfeb ΔIEC ) to examine its importance in defense against injury. UnperturbedTfeb ΔIEC mice exhibited grossly normal intestinal epithelia, except for a defect in Paneth cell granules.Tfeb ΔIEC mice exhibited lower levels of lipoproteinApoA1 expression, which is downregulated in Crohn's disease patients and causally linked to colitis susceptibility. Upon environmental epithelial injury using dextran sodium sulfate (DSS), Tfeb ΔIEC mice exhibited exaggerated colitis. Thus, our study reveals that TFEB is critical for resistance to intestinal epithelial cell injury, potentially mediated by APOA1.